Use of Digital Learning Management Systems for Enhancing Cognitive Achievement in Vocational Productive Course - Suryantoro, Sigit Arif; Muchlas, Muchlas; Santosa, Budi (Journal of Vocational Education Studies, 2024)
The use of digital technology is increasingly widespread, including in the world of education. Observations in the field found that students' understanding of using digital technology to support learning productive lessons in vocational high schools still needed to improve. The study aims to obtain information about (1) the level of students' understanding of the use of digital learning management systems (DLMS); (2) the level of student perception regarding the availability and quality of DLMS use, and (3) the effectiveness of DLMS implementation in increasing students' understanding of productive subjects. This research is a quantitative study with a proportional random sampling technique. The sample was 194 out of 441 students from three state-owned vocational high schools. Data was collected using questionnaire instruments, observation sheets, and documentation. Data credibility is measured using validity, reliability, normality, and homogeneity tests, while data processing techniques use partial significance tests (t-test) and simultaneous tests (F-test). The research results show that students' understanding of DLMS is quite high, and their perception of the availability and quality of available DLMS is at a good level. This research also found that understanding DLMS and perceptions of DLMS as a learning medium can increase students' cognitive achievement in productive subjects.